FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN KE PUBLIK - Jeni Susanti; Made Dana Saputra (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study examined several variables that predicted affect the timeliness of submission of financial statements, the size of the company, size of the firm, the company's profitability and debt to equity ratio. The research object is the Real Estate and Property companies listed on the Stock Exchange which publishes audited financial statements consistently in the years 2011-2015. By using purposive sampling method obtained 46 samples were then tested using regression at a significance level of 5 per cent. This test showed empirical evidence that the variable size of the company, size of the firm, the company's profitability and debt to equity ratio significantly affects the timeliness of the company's financial reporting